Pembangunan Sistem Informasi Persediaan Barang Di Qaisar Mart Berbasis Desktop - Abditio, Abditio (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
Inventory of goods is always needed in Qaisar Mart activities. The existence of inventory on the one hand is a waste so it can be said to be a burden that must be eliminated. The aim of this research is to develop a desktop-based inventory information system at Qaisar Mart. The method in this proposed research is a system development method using the Waterfall method. This method was chosen by researchers because the Waterfall method is a sequential software development method so that there will be no repetition, starting from system analysis, system design, system development and repeated trials so that the time used will be more efficient. A computerized inventory system will be very helpful if implemented because merchandise inventory management becomes easier, and owners can directly monitor their merchandise inventory through tables and reports. The inventory information system held by the admin and owner can find out the inventory of the goods.